Dream To Be Best Balerina In Steven Jacobson`S Center Stage Turn It Up Movie ( 2008 ) : A Psychoanalytic Approach - Agustin, Siti Mucharomah (2012)
The problem statement of this study is how Katte tries to reach her dream. The object of the research is a movie entitled Center Stage Turn It Up by Steven Jacobson. The researcher uses psychoanalytic approach focusing on Sigmund Freud's psychoanalytic theory. The study belongs to qualitative study in which the writer uses two data sources. The primary data source is Center Stage Turn It Up movie directed by Steven Jacobson released in 2008, while the secondary data sources are other materials taken from books, journals, and internet related to the study. From the result of analysis, it can be drawn the following conclusion, firstly, the elements of structural analysis shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography,sound, and editing are related one another and formsa unity. Secondly, based on the psychoanalytic analysis, the writer concludes the conflict mental condition of major character. Happens when there is contradiction between Id, Ego and Superego.